Discourse analysis and media attitudes - Baker, Paul (Cambridge University Press, 2013)
Includes bibliographical references and index; Sketching Muslims: the big picture -- Muslim or Moslem: differences between newspapers -- Effect: change over time -- Welcome to Muslim world: collectivisation and differentiation -- Devout Muslim ways of believing -- From hate preachers to scroungers: who benefits? -- Burqas and brainwashing: Muslims and gender -- Does history rhyme? earlier news representations of Muslims